Priorities for the CMU agenda - Jan Pieter Krahnen; Loriana Pelizzon (Leibniz Institute for Financial Research SAFE, 2020)
The European Commission is trying to reboot the CMU project: The High-Level Forum on Capital Markets Union - a group of 28 selected experts from industry, academia and civil society - is expected to submit policy recommendations by the end of May 2020 which will feed into the Commission's new CMU agenda. This contribution is largely based on a letter to the High-Level Forum that gives feedback on the Interim Report published in February. There, we introduce a comprehensive approach to distinguish, from a functional finance perspective, between the 'game changers' and what is nice to have. We highlight the importance of common and consistent supervisory practices across Member States and recommend building up a European Securities and Exchange Commission (E-SEC) according to the American model.
urn:nbn:de:hebis:30:3-534482
Keywords: 330; CMU; High-Level-Forum; Interim Report